Ordered assemblies of Fe3O4 and a donor-acceptor-type π-conjugated polymer in nanoparticles for enhanced photoacoustic and magnetic effects. (14th January 2019) - Pham, Thi-Thuy Duong; Seo, Young Hun; Lee, Dabin; Noh, Juran; Chae, Jeongwan; Kang, Eunah; Park, JaeHong; Shin, Tae Joo; Kim, Sehoon; Park, Juhyun
Abstract: We report that the ordered structure in the assemblies of iron oxide nanoparticles in conjugated polymer nanoparticles is the key to achieve better properties to realize multimodal theranostic agents for magnetic resonance and photoacoustic imaging. Hybrid nanoparticles of a conjugated polymer (PCPDTBT), a phospholipid (D8PE) with a primary amine polar head, and iron oxide (Fe3 O4 ) nanoparticles were prepared by a phase-separated film shattering process by varying the iron oxide concentration while maintaining a fixed mixing ratio of PCPDTBT and D8PE. Notably, the hybrid nanoparticles assembled at a molar mixing ratio of 1:1:0.8 (PCPDTBT/D8PE/Fe3 O4 ) exhibited the shortest transversal relaxation time, T 2, and a photoacoustic signal 22 times higher than that obtained at the 1:1:0 mixing ratio. Structural analysis by X-ray diffraction together with the measurements of energy transfer by transient absorption spectroscopy confirmed that the structural ordering of these hybrid nanoparticles was responsible for their enhanced photoacoustic and magnetic properties. Graphical abstract: Highlights: Hybrid nanoparticles of a donor-acceptor-type conjugated polymer, iron oxides and a phospholipid. Shattering of phase-separated films produced hybrid nanoparticles. Strongly ordered assembly structures were confirmed by grazing incidence X-ray scattering. Contrast in both photoacoustic and magnetic resonance imaging were significantly enhanced. Ordering and clustering of conjugated polymers and magnetites were responsible for the property enhancement.